Avaliação do uso de diferentes modelos receptores com dados de PM2,5: balanço químico de massa (BQM) e fatoração de matriz positiva (FMP) - Trindade, Camila Carnielli (2009)
The identification of sources of particulate matter has been a topic of growing interest throughout the world to assist the air quality management. This class of studies is conventionally based on the use of receptor models, which identify and quantify the sources responsible from the concentration of the contaminant in the receptor. There are a variety of receptor models, this study compares the results of chemical mass balance (CMB) and positive matrix factorization (PMF) models for a database of PM2.5, for the region of Brighton, Colorado, with a view to investigate the difficulties in the use of each model, as well as its advantages and disadvantages. It is known that the CMB model has the disadvantage of requiring source profiles, determined experimentally, to be applied and also has limitations when the sources involved are similar. On the other hand, the PMF model does not require source profiles, it has the disadvantage to require a large amount sample, in receptor. The results showed, based on performance measures that both models were able to reproduce the data of the receptor with reasonable fit. However, different results were adjusted for performance measurements. The CMB model, used 9 types of sources and PMF model found only 6 types of sources, it was noted by that what the PMF model has difficulty in modeling sources that appear occasionally. The sources ammonium sulfate, soil, diesel vehicles and ammonium nitrate have good correlation in the results of the two model of sources apportionment. The source profiles used in the CMB model and results of the PMF model that present more similarities were of the sources ammonium nitrate, soil, ammonium sulfate and combustion of wood and/or smoker vehicles. It was verified what the PMF model does not separate well species in the source profiles, therefore becomes even more complex to identify the sources in the FMP model, requiring considerable knowledge about the composition of many sources. For the database used with similar sources, the lack of confidence in the results based only on receptors models for a final decision on the source apportionment.